2021
DOI: 10.3389/fnut.2021.797004
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Protein at Breakfast Rather Than at Dinner and Lunch Is Effective on Skeletal Muscle Mass in Older Adults

Abstract: Background: The effects of different intake patterns of meal protein on muscle mass have not been clarified. We cross-sectionally and longitudinally examined the effect of different timing of protein intake on sarcopenia-related factors in older adults.Methods: This cross-sectional study 1 included 219 (male, n = 69, female, n = 150) elderly subjects aged ≥65 years. Subjects who consumed more protein at breakfast than at dinner were grouped into the morning group (MG, n = 76; male, n = 26; female, n = 50), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…The amount, type, and source of proteins, as well as the timing of intake and spreading over the whole day ( 34 ). In the context of morning-evening protein intake, Kim et al ( 35 ) found that supplementation of protein at breakfast rather than at dinner and lunch is effective on skeletal muscle mass in older adults. The study showed that the higher the ratio of morning protein intake relative to the total protein intake, the better the muscle mass and handgrip strength.…”
Section: Discussionmentioning
confidence: 99%
“…The amount, type, and source of proteins, as well as the timing of intake and spreading over the whole day ( 34 ). In the context of morning-evening protein intake, Kim et al ( 35 ) found that supplementation of protein at breakfast rather than at dinner and lunch is effective on skeletal muscle mass in older adults. The study showed that the higher the ratio of morning protein intake relative to the total protein intake, the better the muscle mass and handgrip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Protein intake is especially important in older adults to overcome age-associated muscle anabolic resistance and to regenerate and maintain muscle mass as much as possible [30]. Meat contains essential amino acids and high levels of minerals (e.g., iron, zinc, and selenium) and B vitamins, and even a moderate intake can increase muscle protein synthesis in older adults [15], but meat texture is tough, fibrous, and difficult to chew.…”
Section: Status Of Protein Intake In Older Adultsmentioning
confidence: 99%
“…Badaniu poddano 26 mężczyzn wykonujących RT 3 razy w tygodniu przez 12 tygodni. Wykazano, że w przypadku hipertrofii mięśni wywołanej przez RT u zdrowych młodych mężczyzn, spożywanie posiłku wzbogaconego w białko na śniadanie i mniej białka na kolację przy jednoczesnym osiągnięciu odpowiedniego dziennego PI jest bardziej skuteczne niż spożywanie większej ilości białka na kolację [20]- [22] Badacze wciąż szukają odpowiedzi na pytanie, czy optymalny czas przyjmowania składników odżywczych to przed, czy po RE, zwłaszcza w kontekście ograniczenia MPB dla zwiększonej reakcji anabolicznej mięśni. Kume, Yasuda i Hashimoto przeprowadzili badanie, którego celem była ocena wpływu czasu przyjęcia posiłku o dużej zawartości składników odżywczych i białka w stosunku do czasu wykonania RE.…”
Section: Optymalizacja Momentu Przyjęcia I Dystrybucji Dawek Suplemen...unclassified